MaveDB: an open-source platform to distribute and interpret data from multiplexed assays of variant effect - Esposito, Daniel; Weile, Jochen; Shendure, Jay; Starita, Lea M.; Papenfuss, Anthony T.; Roth, Frederick P.; Fowler, Douglas M.; Rubin, Alan F. (Genome Biology, 2019)
Multiplex assays of variant effect (MAVEs), such as deep mutational scans and massively parallel reporter assays, test thousands of sequence variants in a single experiment. Despite the importance of MAVE data for basic and clinical research, there is no standard resource for their discovery and distribution. Here, we present MaveDB ( https://www.mavedb.org ), a public repository for large-scale measurements of sequence variant impact, designed for interoperability with applications to interpret these datasets. We also describe the first such application, MaveVis, which retrieves, visualizes, and contextualizes variant effect maps. Together, the database and applications will empower the community to mine these powerful datasets.